Análise de Estratégias Linguístico-Discursivas Constitutivas do Gênero Textual "Santinho Político" - Priscila Lopes Viana (2009)
The aim of this research was to identify, to describe and to analyze the constitutive linguistic-discursive-strategies of texts called santinhos políticos. Based on the model of analysis of texts, the theoretical framework of interactionism sociodiscursive proposed by Bronckart (1999), also by some contributions from Charaudeau (2006), Perelman &Olbrechts-Tyteca (2005), Marcuschi ( 2003), and others, we analyzed how persuasive speech of santinhos is built, we defined its architecture text, we identified and described mechanisms of textualization and enunciative mechanisms in them. We understand, in this research, languages are as collective activities because both are built upon interactions. We believe in the success of social activities is related to linguistic choices of agents (producer and reader), so the choice of textual genre, in that the agent-producer will express his ideas, occurs as a selection of the best tool to try to shape the agent reader to give the answer that the agent-producer aims. We seek, therefore, in some way to determine the statute of a textual genre that, as long as we have seen, has not been empirical object by linguistic analysis.